Femininní a maskulinní označení: vliv na hodnocení prestiže - Irena Smetáčková (Gender a Výzkum, 2016)
The labour market is segregated both vertically and horizontally by gender. Some research has concluded that gender segregation results in a lower prestige being attributed to occupations labelled as feminine (Merkel et al. 2012, Formanowicz et al. 2012). On the other hand, gender-sensitive language that uses feminine labels for better contingency with social reality is considered a basic tool for gender equality. This article explores whether in Czech society there are differences in the level of prestige attached to 37 occupations labelled as feminine and masculine. The survey results show (sample of 642 adults that a gender difference exists only in a few occupations. In fields with a real prevalence of men or women the prestige of gender-congruent labelled occupations was significantly higher. Men’s and women’s opinions on occupational prestige are similar; this finding is interpreted in relation to social identity theory and system justification theory.